2012
DOI: 10.1080/10503307.2012.688883
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapist development: Integration as a way to autonomy

Abstract: This study deals with the question of how therapists naturally develop an integrative perspective. A grounded theory analysis was conducted, based on retrospective interviews with seven experienced therapists (working together in the same training program). Adoption of an integrative perspective was found to be an unintended consequence of the development towards an autonomous personal therapeutic approach. This development is directed by two autonomous criteria (congruence and perceived efficacy) and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Scholars of healthcare disciplines are demonstrating a growing interest in better understanding student professional development (PD) during graduate training. Quantitative and qualitative methodologies are increasingly implemented in order to shed light on students' in‐training experience that, in turn, may inform curricula design, supervision and field training policies, as well as guidelines for preparing student transition into the ‘real world’ upon graduation (Orlinsky, Rønnestad, & Ambühl, ; Howard, Inman, & Altman, ; Meredith & Baker, ; Sutherland, Howard, & Markauskaite, ; Carlsson, Norberg, Sandell, & Schubert, ; Klein, Bernard, & Schermer, ; Rihacek, Danelova, & Cermak, ).…”
mentioning
confidence: 99%
“…Scholars of healthcare disciplines are demonstrating a growing interest in better understanding student professional development (PD) during graduate training. Quantitative and qualitative methodologies are increasingly implemented in order to shed light on students' in‐training experience that, in turn, may inform curricula design, supervision and field training policies, as well as guidelines for preparing student transition into the ‘real world’ upon graduation (Orlinsky, Rønnestad, & Ambühl, ; Howard, Inman, & Altman, ; Meredith & Baker, ; Sutherland, Howard, & Markauskaite, ; Carlsson, Norberg, Sandell, & Schubert, ; Klein, Bernard, & Schermer, ; Rihacek, Danelova, & Cermak, ).…”
mentioning
confidence: 99%
“…In this sense, the authors adhered to Charmaz's version of the method, reflecting the fact that their initial assumptions inevitably influenced the research process. Here in particular, the analytical process was a process of interaction between a previously formulated concept of Personal Therapeutic Approach (Rihacek et al, 2012), which provided a basis for the researchers' preexistent understanding, and new data which enabled the researchers to further elaborate and enrich this basic concept and to conceptualize its developmental aspects. By explicating their theoretical orientations, the researchers also admit that a researcher of a dissimilar theoretical perspective may have conceptualized the results in a different way.…”
Section: Discussionmentioning
confidence: 99%
“…Several empirical studies suggest that counselors and psychotherapists tend to form their own, personalized working styles during their professional development (Carlsson, Norberg, Sandell, & Schubert, 2011;Rihacek, Danelova, & Cermak, 2012;Skovholt & Rønnestad, 1992;Vasco & Dryden, 1997). A similar conclusion can be drawn from autobiographic literature (e.g.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…It has been shown that interpersonal sources of influence (i.e., trainers, personal therapists, supervisors, peers, etc.) play a more important role than "impersonal" sources (i.e., books, articles) in psychotherapist development (Rønnestad & Skovholt, 2003) and that the restricting or legitimizing influence of a psychotherapist's reference group may affect his or her attitude toward an orientation or toward integration as such (Rihacek et al, 2012). Fifth, future studies should aim at garnering a better understanding of the nature of personalized working styles in psychotherapists, as this personalization may interfere with adherence to evidence-based treatment models.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%